The Inuit archaeology of the Quebec Lower North Shore - Fitzhugh, William (Études/Inuit/Studies, 2015)
This paper summarizes a decade of archaeological research demonstrating evidence for periods of year-round Inuit occupation of the Quebec Lower North Shore in the late 17th and early 18th centuries. Excavations at several winter villages replicate settlement patterns at sod house sites in central Labrador, including continuation of a traditional Inuit subsistence and domestic economy while incorporating European materials and artifacts. Finds at the Hare Harbour site on Petit Mécatina Island suggest active Inuit collaboration with a European (probably Basque) whaling and fishing station. The Hare Harbour site is a unique early instance of Inuit-European economic and social enterprise. In the early 1700s the Inuit occupation of the Quebec Lower North Shore came to an abrupt end due to economic competition and hostilities with European and Indian groups that forced Inuit to abandon the coast and retreat north to the core area of Inuit settlement on the central Labrador coast.